Evaluation of IL-17 and IL-35 Serum Levels in Patients with Preeclampsia - Batebi, Atefeh (J Reprod Infertil, 2019)
BACKGROUND: Pre-eclampsia (PE) is the most common pregnancy complication affecting 2–8% of all pregnancies. PE could lead to maternal and prenatal morbidity. Imbalanced cytokine network and altered levels of several inflammatory and anti-inflammatory cytokines have been reported in PE. Because of scare information regarding the roles of IL-17 and IL-35 in PE, the current study aimed to investigate the serum level of these cytokines in a group of Iranian women suffering from PE. METHODS: Serum samples were collected from 100 pre-eclamptic and 100 healthy pregnant women. Patients and controls were matched for age, ethnicity and body mass index. The level of IL-35 and IL-17 were evaluated by ELISA technique. T test and one-way ANOVA with Tukey Post-Hoc test were used for analysis and p<0.05 were assumed significant. RESULTS: The serum level of IL-35 was increased in pre-eclamptic subjects as compared with healthy pregnant women (p<0.001). There was no significant difference in the serum level of IL-17 between pre-eclamptic and healthy pregnant women (p=0.73). Moreover, the results of the present study also showed that the pregnant women with severe pre-eclampsia had higher level of IL-35 in their sera when compared to those with mild form of the disease (p<0.001). In addition, the serum level of IL-35 was significantly elevated in women with higher proteinuria (p<0.001). CONCLUSION: Based on the our results, it seems that elevated levels of IL-35 in sera of pre-eclamptic women might work as a marker to evaluate the severity of the preeclampsia.